Peer Separation Anxiety among Final-Year University Students: A Scoping Review from Bowlby's Attachment Theory Perspective - Yohanna Valentina Reva; Uman Suherman; Rina Nurhudi Ramdhani (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
The transition from university to post-academic life represents a critical developmental stage that presents significant challenges to the social well-being of final-year students. From a guidance and counselling perspective, anticipated peer separation may lead to emotional distress, a phenomenon that remains underexplored in higher education research. Peer separation anxiety is defined as excessive emotional distress experienced upon actual or anticipated separation from significant peer attachment figures. This construct is distinct from parental separation anxiety and is increasingly recognised during emerging adulthood. Drawing on Attachment Theory, the present study aims to map and synthesise current evidence regarding peer separation anxiety and its psychological implications among university students. A scoping review was conducted following the Arksey and O’Malley framework and PRISMA-ScR guidelines, utilising the Population–Concept–Context (PCC) framework, and included literature published between 2016 and 2026. The search identified 1,640 records across Scopus, PsycINFO, and Web of Science, of which 8 met the inclusion criteria. The findings indicate that separation anxiety is consistently associated with internalising symptoms such as anxiety and depression. Insecure attachment styles and intolerance of uncertainty are identified as key risk factors, whereas peer attachment functions as a protective factor in psychological adjustment. In collectivist cultural contexts, such as Indonesia, where group identity and interdependence are central, peer bonds formed during university acquire heightened psychological significance. The dissolution of these bonds at graduation constitutes both an interpersonal loss and a disruption of collective identity. Notably, although the review focuses on final-year students, most included studies examined the general university student population rather than those specifically at the point of graduation, highlighting a significant conceptual and population gap.Furthermore, no studies from Indonesia were identified, and research employing qualitative or helping relationship-based approaches is lacking. These findings highlight the urgent need for culturally relevant research and the development of localised evaluation tools. Specifically, adapting the ASA-19 for use in Indonesian higher education should be prioritised to enable guidance and counselling professionals to identify and address peer separation anxiety among graduating students effectively.